Cloudbuster Project Maroc (Christoph Keller Editions, 2010)
Reenactment of the scientific experiments of Wilhelm Reich from 1953-54 to influence the atmosphere by the means of Orgone-energy. Designed by Manuel Raeder Fondation Janelly et Jean Rene Fourtou, Institut de France Printed in Germany
English
Keywords: N8350-8356 Art as a profession. Artists